Pelatihan Pembukuan Sederhana Pada Kelompok Industri Kecil Menengah (Ikm) Kripik Tempe Kilodang Desa Tawangrejo Kecamatan Takeran Kabupaten Magetan Madiun - Kartika Sari, Syarifah Ratih; Wildaniyati, Arini (Universitas Merdeka Madiun, 2020)
The purpose of this community service is to provide an understanding of accounting in general and provide training in the preparation of accounting (financial statements) to owner IKM Kilodang Tawangrejo in Magetan . Since established, this IKM has not had financial report that resulted in Mrs. Suti's tempe IKM and Mrs. Narsi are not being able to know the cash inflows and cash outflows. The benefits of this bookkeeping training are expected through training and mentoring. It is expected that IKM players can make simple bookkeeping and determine. the profit and loss of their business. Increase the income of through information obtained from financial statements. Located in Tawangrejo Takeran, Magetan Regency, which was focused on chips, especially Mrs. Suti and Mrs. Narsi, which was conducted on 1 August 2018 - 31 December 2018. The activities carried out by providing training to IKM actors in making simple bookkeeping that will greatly help them in managing cash, so that they can find out the benefits and losses obtained, so that they can develop their business to become bigger and more resilient. Keywords—: Bookkeeping; IKM.